2017
DOI: 10.3390/v9120384
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage and Structural Transitions during Maturation of Staphylococcus aureus Bacteriophage 80α and SaPI1 Capsids

Abstract: In the tailed bacteriophages, DNA is packaged into spherical procapsids, leading to expansion into angular, thin-walled mature capsids. In many cases, this maturation is accompanied by cleavage of the major capsid protein (CP) and other capsid-associated proteins, including the scaffolding protein (SP) that serves as a chaperone for the assembly process. Staphylococcus aureus bacteriophage 80α is capable of high frequency mobilization of mobile genetic elements called S. aureus pathogenicity islands (SaPIs), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 48 publications
(72 reference statements)
1
19
0
Order By: Relevance
“…This process most likely requires conformational changes in the baseplate in order to expose the hydrolase domains of Tal and Hyd ( Fig 6B). We previously observed that treatment of 80α with heat or low pH led to clustering of baseplates, presumably due to exposure of hydrophobic sequences resulting from a conformational change [16]. The observed conformational differences in the stem between the 80α and ϕ11 RBPs and the phage P68 tail fiber ( Fig 5B and 5C) suggest that the hinge might constitute a pivot point that allows the RBPs to rotate.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This process most likely requires conformational changes in the baseplate in order to expose the hydrolase domains of Tal and Hyd ( Fig 6B). We previously observed that treatment of 80α with heat or low pH led to clustering of baseplates, presumably due to exposure of hydrophobic sequences resulting from a conformational change [16]. The observed conformational differences in the stem between the 80α and ϕ11 RBPs and the phage P68 tail fiber ( Fig 5B and 5C) suggest that the hinge might constitute a pivot point that allows the RBPs to rotate.…”
Section: Discussionmentioning
confidence: 80%
“…80α tails were produced using an 80α lysogen (strain ST247) with a deletion of the first 13 amino acids of the scaffolding protein (gp46), which results in failure to form capsids and accumulation of tails in the lysate ( Fig 1C) [16]. Initial cryo-EM datasets of up to �7,000 baseplate particle images were collected with a Philips CM20 microscope on SO-163 film or using an FEI Titan Krios microscope equipped with a Direct Electron DE-20 detector, and reconstructed with sixfold (C6) symmetry to 9.3 Å resolution (FSC 0.5 ) using EMAN and EMAN2 [17].…”
Section: Three-dimensional Reconstruction Of the 80α Baseplatementioning
confidence: 99%
See 2 more Smart Citations
“…Phage 80α is a typical staphylococcal siphovirus with a 43.8 kbp genome and a 63 nm icosahedral capsid, attached to a 190 nm long flexuous tail that is capped by an ornate baseplate (14)(15)(16). 80α is one of the best-described S. aureus phages, and is closely related to φETA2 and other phages involved in specifying bacterial pathogenicity (14).…”
Section: Introductionmentioning
confidence: 99%